2019
DOI: 10.3390/act8010029
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Enhancement of Bending and Blocking Force of an Ionic Polymer-Metal Composite (IPMC) by the Active Use of Its Material Characteristics Change

Abstract: The exhibition of significantly large bending is a remarkable characteristic of an ionic polymer-metal composite (IPMC). However, its inability to generate a high enough force is a major problem in achieving a practical IPMC actuator. The simultaneous enhancement of bending and force generation is needed for broadening the potential of the IPMC actuator as a practical engineering device. Corrosive materials as a flexible electrode of the IPMC is usually not preferred, whereas a noncorrosive material such as pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…When the bias was reversed, cations migrated from the pores and toward the outer electrodes, minimizing charge storage at the interlayer and thus rapidly creating a compressive force of 2.0 mN. The generated force was more than seven times higher than that of a state-of-the-art bending motion actuator reported in the literature. ,,, The constant force in the plane direction is empowered by the preserved ion concentration gradient at the electrodes because they are in contact with solid-state ion sources …”
Section: Resultsmentioning
confidence: 91%
“…When the bias was reversed, cations migrated from the pores and toward the outer electrodes, minimizing charge storage at the interlayer and thus rapidly creating a compressive force of 2.0 mN. The generated force was more than seven times higher than that of a state-of-the-art bending motion actuator reported in the literature. ,,, The constant force in the plane direction is empowered by the preserved ion concentration gradient at the electrodes because they are in contact with solid-state ion sources …”
Section: Resultsmentioning
confidence: 91%
“…One essential path to minimize electrical noise and crosstalk contamination in the signal acquisition is to use a more corrosive-resistant metal to form the electrode. A high-conductivity metal such as silver (6.21 × 10 7 S/m) has been reported by the literature [23] for bend-sensing and actuating [38,39] applications. Although silver has high conductivity, it is prone to corrosion.…”
Section: Characterization Of the Self-powered Ipmc Sensormentioning
confidence: 99%
“…Although silver has high conductivity, it is prone to corrosion. Tamagawa et al [39] reported that silver with low corrosive-resistance could improve IPMC performance by forming a thicker electrode…”
Section: Characterization Of the Self-powered Ipmc Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly known IEAP is the ionic polymermetal composite (IPMC) which is predominantly used as an actuator. IPMCs are composed of an ionic polymer membrane, typically Nafion, sandwiched between a pair of noble metal electrodes (Nakshatharan et al, 2018;Tamagawa et al, 2019).…”
Section: Types Of Ionic Eapmentioning
confidence: 99%